The Role of The Philosophy of Science in The Development of Student Character Education in High Schools - Anna Damayanti; Jossiselfiah; Siska Wulandari; Syarnubi, Syarnubi (PAI RAFAH, 2026)
Character education is one of the main pillars in shaping a morally upright generation with global competitiveness. The phenomenon of moral degradation and lack of discipline among students has become a serious concern for schools. Therefore, a more fundamental approach is needed through the application of the principles of the philosophy of science in the character education process. According to Jujun S. Suriasumantri, the philosophy of science functions to "critically analyze the foundations of human knowledge and provide direction for the development of science that is meaningful to life." This principle serves as the foundation of this study to examine the extent to which the understanding of the philosophy of science can strengthen character education among high school students. This research aims to analyze the role of the philosophy of science in developing students' character education. The study employed a qualitative approach with a descriptive method through field observations, teacher interviews, and document analysis. The results indicate that understanding the philosophy of science helps teachers instill values of truth, responsibility, and integrity in students. The philosophy of science serves as an epistemological foundation in the character education process, particularly in the era of globalization that is filled with moral challenges. The implementation of the philosophy of science is reflected through learning reflections, critical discussions, and the habituation of ethical values within the school environment.